Elucidation of Semantic Organization in the Brain Using Functional Neuroimaging: A Review - Cato, M. Allison; Moore, Anna Bacon; Crosson, Bruce (Topics in language disorders, 2001)
This article reviews competing theories of semantic organization in the brain, including modular models, unitary models, and the matrix theory, and provides supporting and refuting evidence for each, incorporating examples from the imaging literature. The literature does provide some support for distinct neural substrates that process specific semantic attributes. (Contains references.) (Author/CR)